2006
DOI: 10.1080/01140671.2006.9514392
|View full text |Cite
|
Sign up to set email alerts
|

New model to predict the timing of olive(Olea europaea)flowering: A case study in central Italy

Abstract: The aim of this study was to analyse the statistical relationships among climatic variables and flowering dates for olive species (Olea europaea). Data were collected over 21 years from the study area located in the province of Perugia, central Italy. Flowering was studied through the aerobiological method and daily pollen concentrations (expressed as pollen grains/ m 3 ) were recorded. A new flowering forecasting indicator (modified chilling unit, CUm) is proposed to identify the beginning and the central ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
1
18
1
Order By: Relevance
“…Additionally, our study evaluated fewer flowering dates (21) than the De Melo- Abreu et al (2004) study (83 dates), which may have led to greater variability in our study. Using a different model proposed for Central Italy, Orlandi et al (2006) reported that 86% of the predicted maximum pollen concentration values, a surrogate for flowering date, were within ±5 days of the observed dates.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, our study evaluated fewer flowering dates (21) than the De Melo- Abreu et al (2004) study (83 dates), which may have led to greater variability in our study. Using a different model proposed for Central Italy, Orlandi et al (2006) reported that 86% of the predicted maximum pollen concentration values, a surrogate for flowering date, were within ±5 days of the observed dates.…”
Section: Discussionmentioning
confidence: 95%
“…Physiologically-based models were later developed using phenological records in the Mediterranean Basin to predict the flowering response of olive to temperature (e.g. ; Alcalá & Barranco, 1992;Osborne et al, 2000;Cesaraccio et al, 2004;Orlandi et al, 2006;Motisi et al, 2008, Pérez-López et al, 2008. A potential limitation of many such models is that differences between cultivars were little considered.…”
Section: Study Area and Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…To make calculations, the following formula was used: gdd (i.e., growing degree days) = Σ(T m -T threshold), where "T m" is the daily mean temperature and "T threshold" is the minimum temperature below which biothermic accumulation stops or is reduced to the lowest terms. for the olive, the T threshold value considered was 7.5°C given that all the study areas are characterised by a mesomediterranean climate where optimum threshold ranges are indicated between 5°C and 7°C whereas other studies indicated the higher correlation values from 6°C to 9°C (mancuso 2000; Bongi et al 2002;orlandi et al 2006;ribeiro et al 2006). using the same method, the gdd values were calculated until the start date of flowering to verify possible behaviour differences of various cultivars between initial and maximum intensity of the anthesis phenomenon.…”
Section: Climatic Analysismentioning
confidence: 99%
“…The bulk of studies is based on information from one or a few stations within a limited region (e.g. Orlandi et al, 2006;Moriondo et al, 2001;Alba and Diaz De La Guardia, 1998;Frenguelli et al, 1989;Galán et al, 2005;Fornaciari et al, 1998). Several wider-area studies were also undertaken to aim at more general statistical characteristics of the season, e.g.…”
Section: Introductionmentioning
confidence: 99%